The Performance of Brazilian Biofuels An Economic, Environmental and Social Analysis - Fagundes de Almeida, Edmar (OECD/ITF Joint Transport Research Centre Discussion Papers, 2007)
The increase in the oil price and the worsening of climate change are fostering biofuels programs around the world. Brazil has a long tradition in biofuels. The country is a large-scale producer of ethanol since the 1970s. In 2006, ethanol was responsible for 17% of all vehicle fuel supply in the Brazil. Brazil's ethanol production from sugarcane is also recognized by its economic performance. In 2005, Brazilian government has launched a biodiesel program. The aim of this report is to make a critical review of Brazilian ethanol and biodiesel programs. It provides lessons about the potential competitiveness of biofuels vis a vis traditional fuels. The document also presents the potential social and environmental impacts of the biofuels in Brazil. The analysis made in this report has been based on an extensive literature review on the subject of biofuels in Brazil. Interviews with experts have also been made in order to clarify some particular issues. The report is divided in two parts: the first is focused on ethanol program and the second to the biodiesel. The first part of the report is divided into the following sections: i) economic performance; ii) the environmental performance; iii) the social performance; iv)energy security performance; v) Brazil as a world-class ethanol exporter. The second part of the report is divided into the following sections: i) economic performance; ii) the environmental performance; iii) Brazil as a world-class biodiesel exporter